Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

# find a general solution and check your answer by substitution 10y"+6y'-4y=0

solve bu subsitution method

## Research, Knowledge and Information :

Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

### Problem Set 2: Answer Key Econ 203 Intermediate ...

... Answer Key Econ 203 Intermediate Microeconomics Please show all the work ... both if we want to check our answer: ... MC = TC ′ = y3 − 2y 2 + 10y = 3y 2 ...

no solution. 5. 4x. 4. y. 1 4y. 12 9 (3, 0) 3x. 2 3x. 5x 2x. 9y 3y (4 ... Round your answer to the nearest tenth. 5.0. 1021 ergs. ... Check your solution by any ...

### Geometry and Discrete Mathematics - Scribd

Using Geometry and Discrete Mathematics ... Solution The circumference of the ... Find the coefficient of x10 in the binomial expansion of 2x simplify your answer. 5.

1. -2x2 + y2 + 4x + 6y + 3 = 0 3. x2 + 16y2 -64y = 0 5. x2 + y2 = -4x + 6y ... 20 = 0 b. x2 + y2 - 4y = 0 c. x2 + y2 - 6x - 10y = 2. ... Justify your answer. f ...

### Math 100 | Fraction (Mathematics) | Abstract Algebra

+ 6y −9 = 2y(4y 2 + 3) −3(4y 2 ... 0 , y 0 ), is a solution of the above system if each ... expressing your answer as

### Free Math Worksheets, Word Problems and Teaching Resources

... "><strong><span style="color: red; font-family: &quot;Trebuchet MS&quot;, sans-serif;">Solution: ... 0, can be find using ... and check your answer using ...

### 7 - Puzzle Museum

Answer is: 0 + 1 + 1 + 2 + 3 ... mathematicians were unable to get the correct solution and failed to check the solutions that ... general solution of: ...

### Visual Presentation in Algebra for First Year Students ...

Developing Skills in Algebra for First Year Students. Login ... 4.2y-x+4=0 -2x= -4y-8 ... show all work and show the calculations that check or test your solution ...

### Study Guide

This study guide was created by an elite notetaker. ... If you're having trouble finding our email please check your spam folder Got it, thanks!

## Suggested Questions And Answer :

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### 6x+y−z=−3 ; 29x+5y+3z=6 ; 35x+6y+2z=3

Call the three equations A, B and C. Note that if we double C we get the same constant 6 as B. So we can write B=2C. That is, 70x+12y+4z=29x+5y+3z. So 41x+7y+z=0. Similarly, note that A=-C. That is, 6x+y-z=-35x-6y-2z. So 41x+7y+z=0. And B=-2A: 29x+5y+3z=-12x-2y+2z, or 41x+7y+z=0. So, because we've i

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### 3x+y=4 x+y=0

x + y =0 (solve this for y, you can also solve 3x + y=4 for y but in my opnion the first one is easier ) subtract x from both sides y = -x (substitute this one for y in the other equation) 3x - x = 4 (3x - 1x= 2x) 2x = 4 ( divide each side by 2) x = 2  ( this is one answer, plug this in to

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### How to find equation of the circle passing through (9,1), (-3,-1) and (4,5)

The equation of a circle is more specific: (x-h)^2+(x-k)^2=a^2, where (h,k) is the centre and a the radius. Plug in the points: (9-h)^2+(1-k)^2=(-3-h)^2+(-1-k)^2=(4-h)^2+(5-k)^2=a^2 This can be written (9-h)^2+(1-k)^2=(3+h)^2+(1+k)^2=(4-h)^2+(5-k)^2=a^2 Leaving a out of it for the moment

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### find solution to the recurrence relation

Solving a Recurrence Relation Find the solution to the recurrence relation, a_n = 6a_(n-1) + 11a_(n-2) – 6a_(n-3), given a_0 = 20, a_1 = 5, a_2 = 15 Assuming a solution of the form a_n = c.r^n, then a_(n-1) = c.r^(n-1), a_(n-2) = c.r^(n-2), a_(n-3) = c.r^(n-3) Substituting for the a

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### What will be their present agees?

Every problem has the answer built in. No-one is asking you to make up a process. Use the data given and simple equations, manipulate the equations, and the answer pops out. The sum of the ages of A and his father is 100. When A is as old as his father is now, he will be five times as old as his so

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### find a general solution and check your answer by substitution 10y"+6y'-4y=0

student

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how to solve this system of equations using substitutioin: -4x+y=6, -5-y=21

- 4x + y = 6 - 5x - y = 21   To do this we need to rearrange one of the equations. It doesn't matter which one you choose to rearrange but I will choose the first.    - 4x + y = 6 Let's add '4x' to both sides of the equation so that we have an equation in the

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### Shawn took in \$69.15 in two hours work on Saturday selling Belts for \$8.05 and earrings for \$4.50. How many of each did Shawn sell?

Shawn took in \$69.15 in two hours work on Saturday selling Belts for \$8.05 and earrings for \$4.50. How many of each did Shawn sell? I'm not too sure how ​you are expected to solve this problem. You will end up with a Diophantine Equation (one involving integer coefficients and integer soluti

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### find the general solution of the equation y"-y'-2y=x^2

find the general solution of the equation y"-y'-2y=x^2 Auxiliary eqn   (assuming a solution of the form y = A.e^(mx) ) m^2 – m – 2 = 0 (m – 2)(m + 1) = 0 m = 2, m = -1 1st solution: y1(x) = A.e^(2x) + B.e^(-x) Assume a solution of the form, y = Cx^2 + Dx + E Then

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### What is the diameter of a spiral coil of .65265 inch diameter pipe 100 feet long?

The equation of a spiral in polar coordinates has the general form r=A+Bø, where A is the starting radius of the spiral and B is a factor governing the growth of the spiral outwards. For example, if B=0, there is no outward growth and we just have a circle of radius A. A horizontal line length A re

#### Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
• Start your question with What, Why, How, When, etc. and end with a "?"
• Be clear and specific
• Use proper spelling and grammar